Customer Relationship Management dan Pengaruhnya Terhadap Loyalitas Nasabah Bank: Studi Pada Bank Muamalat Indonesia - M Nur Rianto Al Arif; Titin Nurasiah (Faculty of Economic and Business, 2015)
Customer Relationship Management and Its Influence on customer loyalty Bank: A Case Study of Bank Muamalat Indonesia. The aim of this research is to analyze the influence of customer relationship management (CRM) to customer’s loyalty. Data collection is using primary and secondary data. The sampling method that used on this research is accidental sampling with 100 respondents. The analysis method on this research is multiple regressions. The CRM variables that used on this research are identify, acquire, retain, develop, and sustainable marketing. From the result, show that the CRM variable had an impact simultaneously on customer’s loyalty. Otherwise, only three variables had an impact on customer’s loyalty, such as acquire activity, retain, and sustainable marketing. There are also show that only acquire variable had an dominant influence on customer’s loyalty in Bank Muamalat Indonesia branch Slipi-Jakarta, because it has the largest coefficient value.DOI: 10.15408/ess.v5i1.2332